Modern Medical Genetics and Genomics - Gomy, Israel (IntechOpen, 2019)
The field of medical genetics and genomics has been constantly revolutionized by new breakthroughs, which bring more knowledge into the etiology and help improve the health care of individuals with either rare or common diseases. Nevertheless, as technologies evolve, novel challenges emerge, both technically and ethically, so they must be prudentially addressed. Among the myriad applications of genomics in medicine, this book depicts a glimpse of the advances achieved that have been leading us to the personalized/precision medicine era.